Factorial Design for the Effect of Ultrasound-Assisted Extraction (UAE) of Labisia pumila sp. in 25-L Mobile Extractor - Nuri Adilah Nashrulmillah, Idris; Ahmad Ziad, Sulaiman; Azilah, Ajit (AENSI Publishing, 2017)
Labisia pumila sp. is one of the herbs that have been widely utilized among Malay women in Malaysia. Traditionally, it is used as postpartum medication, health tonic and for body strength. In this study, a 2 -level factorial experimental design was used to investigate the contribution of the main effect for the extraction of gallic acid in Labisia pumila sp. during ultrasound-assisted extraction (UAE) processes. The factors that have been preliminary screened were material to solvent ratio (1:20 and 1:40), temperature (50-80⁰C), duty cycles (0-50%) and extraction time (4-8 hours) and validated statistically by analysis of variance (ANOVA). The extracts were analyzed by HPLC-DAD using a marker compound, gallic acid. This study was found that the duty cycle was the most influential factor and followed by the extraction time and temperature. All interactions between the studied factors were significant at 95% confidence level. Based on the results, the maximum yield of extraction was obtained with a temperature 80⁰C, extraction time of 8 hours, the material to solvent of 1:20 and duty cycle 50%. At these conditions, extraction yield value determined as 105.731 ± 8.633mg GAE/g dry weight. The experimental values under optimal condition were in a good consistent with the predicted values. Overall, the results obtained gives useful directions on how to improve recovery by proper selection of extraction condition.